Porous polyethylene for tissue engineering applications in diabetic rats treated with calcitonin: Histomorphometric analysis - Claro, Flávio Augusto; Lima, José Roberto Sá [UNESP]; Salgado, Miguel Angel Castillo [UNESP]; Gomes, Mônica Fernandes [UNESP] (My University, 2005)
Purpose: The purpose of this work was to study the bone tissue reaction after porous polyethylene (Polipore) implantation into surgical defects in the parietal bones of rats with streptozotocin-induced diabetes, treated with salmon calcitonin. Materials and Methods: Porous polyethylene implants were placed in bone defects created in 36 adult female rats. The rats were divided into 3 equal groups: diabetic treated with calcitonin (DCa), diabetic (D), and control (C). The animals of the DCa group received applications of salmon calcitonin on alternating days immediately after the surgery until sacrifice. The rats were sacrificed after 15, 30, 60, and 90 days, and the defects were examined histologically and statistically through histomorphometric analysis. Results: Histomorphometric analysis showed that there was no statistically significant difference in the mean quantity of inflammatory cells among all study groups after 15 and 90 days. At 30 days, a statistically significant difference was observed between the D and C groups and the D and DCa groups. At 60 days, there was no statistically significant difference between the D and DCa groups. Discussion: Porous polyethylene can be considered an option for implant material when there are investigations that prove its biocompatibility and stability in the host tissues. Salmon calcitonin positively aided the bone repair and attenuated the inflammatory response until 30 days after the surgery. Conclusion: Porous polyethylene was tolerated by the host tissues in all groups, and moderate chronic inflammatory reaction was observed up to the 90-day period. Salmon calcitonin attenuated the inflammatory response up until 30 days.
Keywords: Bone repair; Diabetes mellitus; Porous polyethylene; Salmon calcitonin; Streptozotocin; polyethylene; salcatonin; animal model; animal tissue; bone tissue; controlled study; female; implant; implantation; inflammatory cell; morphometrics; nonhuman; porosity; rat; skull defect; statistical significance; streptozocin diabetes; tissue engineering; Animals; Biocompatible Materials; Bone Diseases; Bone Substitutes; Calcitonin; Connective Tissue; Diabetes Mellitus, Experimental; Female; Giant Cells; Granulation Tissue; Injections, Subcutaneous; Lymphocytes; Macrophages; Parietal Bone; Polyethylene; Porosity; Rats; Rats, Wistar; Streptozocin; Time Factors; Tissue Engineering; Wound Healing